2014
DOI: 10.1093/brain/awu015
|View full text |Cite
|
Sign up to set email alerts
|

NaV1.4 mutations cause hypokalaemic periodic paralysis by disrupting IIIS4 movement during recovery

Abstract: Cations leaking through the voltage sensor of mutant sodium or calcium channels underlie hypokalaemic periodic paralysis. Groome et al. use muscle fibre recordings, voltage clamp, and molecular dynamics, to investigate recently discovered Nav1.4 channel mutations. They identify a novel voltage sensor movement that may explain the muscle pathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
82
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(85 citation statements)
references
References 32 publications
(45 reference statements)
2
82
1
Order By: Relevance
“…Consistent with this hypothesis are findings from molecular dynamics simulations for rNa V 1.4 and rR1128C channels in silico, predicting that a limited translocation of the voltage sensor brings the third arginine in DIIIS4 through the gating pore constriction. 11 While our results show that increased charge movement for R3C at sub-threshold voltages is correlated with enhanced closed-state inactivation, it remains to be discerned what mechanisms couple that movement to the inactivation process. During recovery of skeletal muscle sodium channels, some portion of the activated gating charge is slow to return to a hyperpolarized favored position, a phenomenon termed charge immobilization.…”
Section: Resultsmentioning
confidence: 58%
See 4 more Smart Citations
“…Consistent with this hypothesis are findings from molecular dynamics simulations for rNa V 1.4 and rR1128C channels in silico, predicting that a limited translocation of the voltage sensor brings the third arginine in DIIIS4 through the gating pore constriction. 11 While our results show that increased charge movement for R3C at sub-threshold voltages is correlated with enhanced closed-state inactivation, it remains to be discerned what mechanisms couple that movement to the inactivation process. During recovery of skeletal muscle sodium channels, some portion of the activated gating charge is slow to return to a hyperpolarized favored position, a phenomenon termed charge immobilization.…”
Section: Resultsmentioning
confidence: 58%
“…11 In that study, we found that action potentials in R1135H patient muscle fibers were slow to develop and reduced in amplitude. Expression of that mutation and a novel R1135C mutation in mammalian cells and in oocytes revealed gating defects that include enhancement of fast and slow inactivation, prolonged recovery, depolarization-induced outward omega current and impaired deactivation.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations